Strategic Imperatives of National Defense System: The Ideal Indonesian Defence Posture Development Program in the Natuna Islands - KBG Sumudu Madutharanga; Fauzia Gustarina Cempaka Timur; Surachman Surjaatmadia (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract This article aims to explore the imperative of developing an ideal defence posture for the Natuna Islands, a strategically significant region for Indonesia's sovereignty and geopolitical interests. The proposed defence posture program involves a comprehensive strategy encompassing strengths, capabilities, and titles across both military and non-military dimensions. In terms of strength, a robust naval presence, technological advancements, and international collaborations are pivotal components. Modernizing naval assets, employing cutting-edge surveillance technologies, and engaging in joint exercises with global partners enhance Indonesia's maritime strength. Capability aspects extend beyond military prowess to encompass economic resilience, diplomatic finesse, and environmental stewardship. Investments in naval and air defence capabilities are complemented by economic development projects, sustainable resource management, and diplomatic initiatives, collectively fortifying the Natuna Islands' overall capabilities. The title aspects involve legal recognition and psychological alignment. Diplomatic efforts focus on securing international acknowledgment of Indonesia's sovereignty over the Natuna Islands, adhering to international laws and fostering positive relationships with neighbouring nations. Domestically, creating a sense of national identity and ownership contributes to the psychological title, aligning public sentiment with strategic imperatives. In the military domain, a holistic defence posture involves modernizing air and ground forces, establishing robust cyber defences, and ensuring the overall readiness of Indonesia's armed forces. Non-military aspects of the defence posture development program emphasize economic growth, diplomatic collaboration, and environmental sustainability. Leveraging the strategic location of the Natuna Islands for economic development, engaging in diplomatic dialogues with neighbouring nations, and implementing sustainable practices contribute to a comprehensive defence strategy. Keywords: Defence Posture, Natuna Islands, Sovereignty, Geopolitical Interests, Strength Aspect, Capability Aspects, Title Aspect, Diplomatic Initiatives